Cuckoo / Mohamad Asyreeq Ashari - Ashari, Mohamad Asyreeq (2021)
Cuckoo E-Brandstore Shah Alam was established on May 21, 2021, by me, Mohamad Asyreeq bin Ashari. I am a Bachelor' s Degree of Health Administration student from the facutly business management University Teknologi Mara (UiTM) who has been given a Social Media Portfolio Assignment. In this project, I was required to build a new business using Facebook as an internet platform. Hence, I made the decision to become an agent for Cuckoo products and services. Various products and services are to be sold in my e-brandstore and I mainly serve my customers by selling and promote CUCKOO products. I am required to manage customer expectation and reach customer satisfaction. I play an important role in achieving sales target by creating strategic planning together with company.